Scientific foundations of sports training planning: a new methodological approach - A.P. Kizko (Theory and Practice of Physical Culture, 2023)
Objective of the study was to theoretically substantiate the application of the theory of oscillations in optimizing the planning of the training process. Results and conclusions. The author argues that the generally recognized dynamics of the phases of the sports form does not correspond to the conditions for the implementation of the optimal (best among many others) options for the development of the physical abilities of the body of athletes, but is the result of the historically established practice of planning sports training. A theoretical substantiation of the use of the theory of fluctuations in the planning of the training process is given, in particular, taking into account the supercompensatory phenomenon in the functional state of the athlete’s body.